The Efficacy of Laparoscopic Cholecystectomy in Patients Suffering from Acute Cholecystitis - SHAH, SYED MUHAMMAD SHAH; ARIJA, DHARMOON; MIRANI, SHAHID HUSSAIN; NAEEM, MUHAMMAD; SHAFQATULLAH; ANJUM, INAYAT HUSAIN (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Acute cholecystitis is one of the most common occurring gall bladder conditions requiring surgical removal. Objective: To assess the efficacy of laparoscopic cholecystectomy in patients suffering from acute cholecystitis. Study Design: Prospective comparative study Place and Duration of Study: Department of Surgery Unit-2, Gulab Devi Hospital, Lahore from 1st March 2023 to 31st August 2023. Methodology: One hundred and ten patients were enrolled. Those patients within the age group of 20-65 and suffering from acute cholecystic were included. A total of 80 patients under went laparoscopic procedure while 20 patients undergo open cholecystectomy (initially 30 but later converted to laparoscopic cholecystectomy). The clinical diagnosis was based on the physical finding’s pf right upper quadrant tenderness, leukocytosis ≥12,000/ml, guarding/rebound, as well as the gross morphological diagnosis intraoperatively. The patients were divided into two groups as laparoscopic and open cholecystectomy. In each patient’s outcome comparison between open a laparoscopic cholecystectomy was performed on the basis of the mean patient age, operative time, hospital stay, complication rate. Results: The mean age of laparoscopic cholecystectomy and open cholecystectomy group patients was 42.41 and 46.39 years respectively. The female’s ratio was way above males with 93.75% in laparoscopic cholecystectomy group and 85% in open cholecystectomy group. The Complication comparison within the two groups presented increased risk of respiratory and gastrointestinal complications in open cholecystectomy group verses laparoscopic cholecystectomy group. There was increased bleeding risk at operation theatre table in open cholecystectomy group in addition to the urinary and wound infection. However, the open cholecystectomy group has significantly lower risk of intra operative bleeding as well as common bile duct injury in comparison to the laparoscopic cholecystectomy group. The comparison of operational time and hospital stay showed within laparoscopic and open cholecystectomy showed a significant decrease in the operational time (129±38 vs 157±34 min) as well as length of hospital stay (2.81±2.17 vs 9.29±6.55 days) in laparoscopic surgery than open surgical protocol for acute cholecystectomy. Conclusion: Laparoscopic cholecystectomy is emerging as a reliable, safe, and cost-effective procedure for treating acute cholecystitis. Complications and mortality rates are generally lower for laparoscopic cholecystectomy compared to open cholecystectomy